Academic Electronic Health Records (SimChart): The Impact on Student Nurse Training - RN, Russell, Bria; Priscilla, Okunji (International Journal of Educational Studies, 2025)
This research report explored the background and significance of integrating an academic EHR system into nursing education to enhance the learning experience and prepare future nurses for real-life clinical practice. Additionally, secondary data was analyzed from researchers who surveyed junior and senior nursing students who had piloted an academic EHR system. The secondary data was categorized into a pre- and post- survey format and then compared via graphs, tables, and written discussion. To understand the need for this study, it is essential to know that in 2009, there was a legislative push for more universal electronic health records and systems within healthcare settings (Williams et al., 2021). This legislative decision led to more and more healthcare systems converting to an electronic system for record-keeping and documentation. This shift would naturally make its way into the nursing curriculum, as it is noted that nurses make up a vast majority of individuals who provide healthcare services (Williams et al., 2021). The need for research within nursing curricula using EHR systems was not only inevitable but of great significance. The times change, and the future of healthcare needs to stay current. The research emphasized the significant benefits of incorporating EHR systems into nursing education. By providing students with hands-on experience using EHR systems, nursing programs can better prepare students for the realities of modern healthcare settings. EHR systems in nursing education help students develop essential skills in documentation, information retrieval, and critical thinking, which are crucial to delivering safe and effective patient care. (Kleib et al., 2021). In addition to highlighting the benefits, the study highlighted several challenges in implementing academic EHR systems into nursing programs. These challenges include faculty training, technical support, and infrastructure for integrating EHR systems into the curriculum (Ellis et al., 2020). Moreover, ensuring EHR systems align with nursing program objectives and accreditation standards was identified as a critical consideration for successful implementation. These limitations within the study yield reasoning for the need for further research while not taking away the grave benefits discovered in the reviewed research and secondary datasets. This study underscores the importance of integrating EHR systems into nursing education to better prepare students for their future roles as healthcare professionals. By addressing the challenges and maximizing the benefits of academic EHR systems in nursing programs, institutions can enhance the quality of nursing education and ultimately improve patient outcomes.